Influence of collection substrate and extraction method on the speciation of soluble iodine in atmospheric aerosols. (January 2019) - Yodle, Chan; Baker, Alex R.
Abstract: The extraction into aqueous solution of total soluble iodine (TSI), iodide and iodate were examined as a function of extraction times between 5 and 60 min for two different extraction methods and from two types of commonly used aerosol collection substrates. The extraction methods tested were ultrasonic agitation and mechanical shaking, while the substrates were cellulose fibre (CF) and glass fibre (GF). Tests were carried on substrates spiked with known amounts of iodide and iodate and on a pair of ambient aerosol samples collected at the University of East Anglia on both substrates over the same time period. The combination of ultrasonic agitation and CF substrates (which has been used in many published studies of aerosol iodine speciation) was shown to lead to variable recovery of iodine species and changes in speciation over extraction time. Mechanical shaking of GF substrates gave good recoveries of iodide and iodate from spiked experiments and stable speciation with time for the ambient aerosol sample. This combination is recommended for future use in the determination of aerosol iodine speciation. Mechanical shaking also appeared to be preferable to ultrasonic agitation for samples that were collected on CF substrates. The optimised conditions (mechanical shaking of GF substrates for 30 min) were applied to the analysis of samples collected during the Stratospheric ozone: Halogen Impacts in a Varying Atmosphere (SHIVA) cruise in the South China and Sulu Seas in November 2011. The results obtained showed variable proportions of iodide, iodate and soluble organic iodine species in these samples, with iodide concentrations possibly related to airmass history and background chemistry. Highlights: Aerosol iodine speciation determined by commonly used methods found to be unreliable. Optimum method tested used glass fibre filters and 30 min of mechanical agitation. Optimum method was applied to samples collected over the northwest Pacific Ocean.